2023
DOI: 10.34306/att.v5i1.288
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Oil Palm Companies Based on Barcode System through Fit Viability Approach: Long Work as A Moderator Variable

Abstract: Novelty technology will be capable of increasing the performance company's coconut palm oil, one of them being the barcode system. So from that, I needed something to study to know how to influence suitability, continuity and use of the barcode system against the performance company coconut palm. Study this using a long working variable as a moderator variable. The study aims to analyze the effect of fit, viability, and use on the performance of a business company's coconut palm based on the Barcode System. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 20 publications
(20 reference statements)
2
14
0
7
Order By: Relevance
“…PT Langkat Nusantara Kepong (LNK) adalah sebuah perusahaan yang bergerak di bidang kebun kelapa sawit dan memiliki karyawan yang bekerja dengan berbagai latar belakang dan keterampilan. Oleh karena itu, penting untuk melakukan pengabdian kepada masyarakat untuk meningkatkan motivasi karyawan di PT LNK agar dapat mengoptimalkan potensi mereka dan meningkatkan kinerja perusahaan secara keseluruhan (Zulham et al, 2023).…”
Section: Pendahuluan Analisis Situasi Permasalahanunclassified
“…PT Langkat Nusantara Kepong (LNK) adalah sebuah perusahaan yang bergerak di bidang kebun kelapa sawit dan memiliki karyawan yang bekerja dengan berbagai latar belakang dan keterampilan. Oleh karena itu, penting untuk melakukan pengabdian kepada masyarakat untuk meningkatkan motivasi karyawan di PT LNK agar dapat mengoptimalkan potensi mereka dan meningkatkan kinerja perusahaan secara keseluruhan (Zulham et al, 2023).…”
Section: Pendahuluan Analisis Situasi Permasalahanunclassified
“…Furthermore, similar analysis using the Naive Bayes algorithm produced an accuracy score of 83.06% [9]. Another study compared the accuracy of Naive Bayes, C4.5, and Random Forest for classifying online motorcycle taxi services [10]. The comparison results showed that Naive Bayes accuracy was better than C4.5 and Random Forest accuracy with an average Naive Bayes accuracy of 69.18%, while Random Forest was 69.18%: 66.34% and C4.5 of 65% [11][12].…”
Section: Iics Semnastik 2023mentioning
confidence: 99%
“…Smart contracts are computer programs that run across the entire Blockchain network to execute transactions and fulfill contract requirements automatically without the need for human intervention [26]. To understand the Blockchain framework, please refer to Figure 3 Country Framework [27] 2023 China Ethereum [28] 2021 Saudi Arabia Chain of Trust [29] 2021 Thailand European Interoperability Framework [30] 2021 -Blockchain Publik [31] 2022 Dubai (UAE) Hyperledger Fabric, CORDA, Ethereum [32] 2020 European Union (EU) Hyperledger Fabric [33] 2019 -Ethereum [34] 2019 Russia - [35] 2022 China - [36] 2023 China License Accountability and Compliance (LAC): OpenChain dan Hyperledger Composer [37] 2021 China [38] 2023 India Blockchain diizinkan : Hyperledger Fabric, R3 Corda, Quorum [39] 2019 Netherlands Blockchain diizinkan: Hyperledger Fabric, Corda, dan Quorum [40] 2021 Indonesia Blockchain Privat: Hyperledger Fabric dan Corda Enterprise [41] 2021 Mexico Blockchain Privat: Hyperledger Fabric dan Corda Enterprise [42] 2022 Korea - [43] 2023 China - [44] 2020 Iran - [45] 2020 Dubai (UAE) Hyperledger Fabric [46] 2021 Brazil -…”
Section: Blockchain Framework In Governmentmentioning
confidence: 99%